Educating Consumers on Transaction Security and Data Privacy in Digital Marketing - Irham Pakkawaru; Abdul Jalil; Nuriatullah; Rizki Amalia; Dede Arseyani Pratamasyari; Noor Riefma Hidayah; Freddy Herdian (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2025)
This community service activity aims to improve community digital literacy, especially in terms of transaction security and personal data protection in digital marketing activities. The activity was carried out in Kayumalue Ngapa Village, North Palu District, with an educational-participatory approach involving residents, MSME players, and digital media users. The implementation of the activity was carried out through several stages, namely initial observation, interactive lectures, educational video screenings, as well as discussion and question and answer sessions. The results of the activity showed an increase in public understanding and awareness of the importance of maintaining digital data security, as well as the emergence of a more cautious attitude in online transactions. Participants welcomed the simple, visual, and applicable method of delivering the material. This activity shows that participation-based education is effective in building collective awareness of cyber threats, and needs to be continued with further technical training to strengthen the community’s practical ability to deal with digital risks.